Biotics in pediatrics: Separating hype from reality - Hania Szajewska (Elsevier, 2024)
The gut microbiota has gained significant attention in research and the media for its role in health and disease. Dysbiosis, an imbalance in gut microbiota composition and function, is increasingly recognized as a contributing factor in the development of various gastrointestinal and extraintestinal conditions. In this growing understanding, biotics (probiotics, prebiotics, synbiotics, and postbiotics) have become a significant industry in many countries. Aggressive marketing often creates confusion, contributing to a gap between hype and reality regarding the effective use of these biotics. This article offers a concise overview of the current consensus definitions for various types of biotics. It will also review existing evidence on the effectiveness of different biotics in preventing and treating diseases in the pediatric population. Doing so will separate the hype from the reality, providing a balanced view of the benefits and limitations of biotics in pediatric care.